PENGEMBANGAN APLIKASI UNTUK MENDETEKSI PERGERAKAN SENDI PADA PASIEN PASCA STROKE MENGGUNAKAN SENSOR ACCELEROMETER DI SMARTPHONE ANDROID - Ryan Ari Setyawan (Universitas Janabadra, 2018)
Stroke is one of the number one killer diseases in Indonesia. Basic health research data in 2013 showed there were 12 people with stroke per thousand (1000) Indonesian population. Rehabilitation of post-stroke patients is one of the efforts to improve the quality of life of stroke patients. This study aims to detect every movement of the joints using accelerometer sensors in post-stroke patients to monitor the progress of the rehabilitation process. Accelerometer sensor test results can be used as an application for joint detection, the application can be used as a tool for the process of therapy or rehabilitation of patients post-stroke. The performance of sensor accuracy can work well with 450 slope angle reference at first movement will be read with number 1 and the next 450 corner will be read with n+1 . Keywords : Accelerometer, Range of Motion, Sendi Atas, Sendi Bawah, Stroke